Industrial training report: Lembaga Tabung Haji. Special project: The factor of crop production in Malaysia - Zairul Azman, Muhammad Danial Farhan (Universiti Teknologi MARA, Perlis, 2024)
I am eager to integrate my practical experience and academic knowledge in the last semester as my degree comes to an end. I have a strong foundation in finance, marketing, and administration thanks to my extensive education and practical experience at Lembaga Tabung Haji. This last semester offers me the chance to use everything I've learned and hone my abilities even more, setting me up for success in my future profession. I have gained essential expertise in Finance, Marketing, and Administration & Hajj departments during my internship journey at Lembaga Tabung Haji. My skill set has expanded as a result of this varied exposure, and I now have a deeper knowledge of how various organizational components collaborate to accomplish shared objectives. In the Finance department, I honed my skills in financial management and customer service. Serving depositors was a key responsibility, where I ensured their needs were promptly and efficiently addressed. This role required a keen eye for detail, strong communication skills, and the ability to manage multiple tasks simultaneously. Ensuring depositor happiness was essential and I took pride in upholding excellent service standards that established strong, trusting relationships with our customers. Transitioning to the Marketing department, I embraced the opportunity to contribute to various promotional campaigns. One of the highlights was participating in the widely recognized Jom Heboh program. This experience allowed me to engage with diverse audiences, enhancing brand visibility and promoting Tabung Haji’s services. I also took part in university outreach initiatives and collaborated with various agencies, expanding our reach and impact. And one of the most rewarding aspects of my career at Tabung Haji has been my involvement in the Administration & Hajj department. I played a pivotal role in the Operasi Haji Tanah Air (OHTA), an operation dedicated to arranging and sending pilgrims to board flights to Mecca. This operation was held at Movenpick Sepang and involved collaboration with numerous stakeholders, including KLIA, MHCC, and bus service companies. Coordinating such a large-scale operation demanded meticulous planning, strong organizational skills, and the ability to work under pressure. Ensuring that every detail was flawlessly executed was crucial to the success of the operation and the satisfaction of the pilgrims.